Asset Management System (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The hotel and restaurant management system is all about managing a business in the hospitality industry that provides high-quality customer service to provide a smoothly functioning system. It pictures out the step-by-step process of every department. The proponents interviewed key people in the company to know the business plan and how to operate the whole process. Part 2 of the asset management system isLogistic 2. The hotel and restaurant business suffered in monitoring and recording of assets because the process is time-consuming and has a disadvantage of loss of records due to papers’ durability, which is mostly used for recording. The proponents developed a web-based system that facilitates and stores the managing functioning of the company. This system will assist in creating while functioning and maintaining things of value to an entity or group. It may apply the systematic process of operating, maintaining, upgrading, and disposing assets effectively, as well as faster auditing. The system executed a unique tag for every asset, which is used to determine the details of each asset. The method used by the proponents was agile software development, which is a systematic theoretical analysis that is applied in developing and completing the project, it is which requirements and solutions solve through the effort of self-organizing and cross-functional teams and/or customers or end-users. The outcome of the project was connected to maintenance, repair, and overhaul that gives a vehicle status. Project management gives a real property, procurement notifies receive, room facilities for the status of the asset, audit management for audited assets, vehicle and fleet management for asset vehicle information, and waste management to dispose of an asset. Future researchers will benefit from this study by sharing significant information that will help them obtain knowledge about asset management systems. It gives the planning asset, negotiates contracts with vendors, sets up assets for users, applies the asset use activity, disposes of assets information, generates accurate reports, and classifies the asset and user-friendly system.
Keywords: agile, cross functional